MRI in Tuberous Sclerosis with Normal I.Q. - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The number, size and distribution of cerebral hamartomas determined by MRI in 11 patients with tuberous sclerosis and normal intellect are reported from the Bath Unit for Research into Paediatrics, Royal United Hospital, Combe Park, Bath, Avon, England and Bristol MRI Centre, Frenchay Hospital, Bristol.